2019
DOI: 10.1101/587154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bipartite anchoring of SCREAM enforces stomatal initiation by coupling MAP Kinases to SPEECHLESS

Abstract: Cell-fate in eukaryotes is regulated by MAP Kinases (MAPKs) that translate external cues to cellular responses. In plants, two MAPKs, MPK3/6, regulate diverse processes of development, environmental response, and immunity. Yet, the mechanism bridging these shared signaling components with a specific target remains unresolved. Focusing on the development of stomata, epidermal valves for gas exchange and transpiration, we report here that the bHLH protein SCREAM functions as a scaffold by recruiting MPK3/6 to do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…However, given that phyB mutants are defective and hy5 mutants are not, it would indicate that HY5 is not an integral component of light regulated stomatal development. The recent studies that have shown that ICE1 is a target of COP1 and ICE1’s pivotal role in regulating SPCH could account for some aspects of light mediated stomatal development (8, 34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, given that phyB mutants are defective and hy5 mutants are not, it would indicate that HY5 is not an integral component of light regulated stomatal development. The recent studies that have shown that ICE1 is a target of COP1 and ICE1’s pivotal role in regulating SPCH could account for some aspects of light mediated stomatal development (8, 34).…”
Section: Discussionmentioning
confidence: 99%
“…These transcription factors form dimers with the bHLH proteins ICE1 and SCRM2 to regulate target genes (6). A ligand/receptor/MAP kinase pathway negatively regulates stomatal development by targeting the SPCH-ICE1 dimer (7, 8). Stomatal lineage cells produce secreted peptides (EPF1 & EPF2), which bind a receptor complex that includes members of the ERECTA family (ERf), the TOO MANY MOUTHS (TMM) receptor-like protein and members of the SERK family of receptor kinases (9, 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions and regulatory consequences of dimerisation between group Ia and group III bHLHs may also be species specific. Recent work from Putarjunan et al (2019) showed that AtICE1/ SCRM is not only required to promote SPCH function, but also acts as a scaffold to link AtSPCH with the MAPKs (MPK3 and MPK6) that negatively regulate it. Both AtICE1/SCRM's positive and negative roles in promoting stomatal initiation are dependent on its MAPK binding domain (KiDOK).…”
Section: Reviewmentioning
confidence: 99%
“…Downstream of the putative EPFL and TMM/ERf ligandreceptor complex in Arabidopsis is the MAPK cascade, headed by the triple kinase (MAPKKK) AtYODA, followed by MAPK kinases MKK4 and MKK5, and MPK3 and MPK6 (reviewed in Pillitteri & Dong, 2013). At stomatal lineage initiation, this culminates in the aforementioned negative regulation of AtSPCH via AtICE1 scaffolding (Putarjunan et al, 2019), but the cascade also regulates proliferation and patterning at later steps in stomatal development, as revealed by cell-type-specific disruption (Bergmann et al, 2004;Lampard et al, 2009). At the cellular level, AtYODA mutant defects were traced to misregulation of asymmetric divisions beginning in the embryo (Lukowitz et al, 2004) and continuing throughout the life of the plant, ultimately leading to severe growth defects, loss of stomatal one-cell spacing, and sterility (Bemis et al, 2013).…”
Section: Conservation and Specialisation Of Receptors And Mapk Modulementioning
confidence: 99%